THE INFLUENCE OF SELF-EFFICACY, FINANCIAL MANAGEMENT, AND INVESTMENT KNOWLEDGE ON INVESTMENT INTEREST AMONG GENERATION Z STUDENTS AT UNIVERSITAS MAHKOTA TRICOM UNGGUL - Frans Gidion Sinuhaji (Jurnal Mahkota Bisnis (Makbis), 2025)
This study examines the influence of self-efficacy, financial (money) management, and investment knowledge on investment interest among Generation Z students at Universitas Mahkota Tricom Unggul. The research employs a quantitative approach using multiple linear regression analysis. The results of the F-test indicate that self-efficacy, money management, and investment knowledge simultaneously have a significant effect on students’ interest in investing (F = 15.520; Sig. = 0.000), confirming that the regression model is statistically fit. The coefficient of determination (R² = 0.445) shows that 44.5% of the variation in investment interest can be explained by the independent variables, while the remaining 55.5% is influenced by other factors outside the model. The Adjusted R Square value of 0.417 suggests good explanatory power. The Durbin–Watson value of 0.720 indicates no serious autocorrelation in the residuals. Overall, the findings highlight the importance of enhancing investment knowledge, financial management skills, and self-efficacy to increase investment interest among Generation Z students. These results provide practical implications for universities and policymakers in designing financial education and investment literacy programs.